Modeling anaerobic co-digestion of water hyacinth with ruminal slaughterhouse waste for first order, modiﬁed gompertz and logistic kinetic models - Erick Auma Omondi; Peter Kuria Ndiba; Gloria Koech Chepkoech; Arnold Aluda Kegode (International Journal of Renewable Energy Development, 2023)
Water hyacinth (Eichhornia crassipes), an invasive aquatic weed with large biomass production is of socio-economic and environmental concern in fresh water bodies such as the Lake Victoria in East Africa. Efforts towards its control and removal can be complemented by biogas production for use as energy source. The co-digestion of water hyacinth (WH) with ruminal slaughterhouse waste (RSW) has the potential to improve biogas production from WH through collation of processes parameters such as the C/N and C/P ratios, potassium concentration and buffering capacity. Knowledge of optimum proportion of the RSW as the minor substrate is of both process and operational importance. Moreover, efficient operation of the process requires an understanding of the relationship between the biogas production and the process parameters. Kinetic models can be useful tools for describing the biogas production process in batch reactors. While the first order kinetics models assume that the rate of biogas production is proportional to the concentration of the remaining substrates, other models such as the modiﬁed Gompertz and the Logistic models incorporate the lag phase, a key feature of the anaerobic digestion process. This study aimed to establish the optimum proportion of RSW in co-digestion with WH under mesophilic conditions, and apply kinetics models to describe the biogas production. The study conducted batch co-digestion of WH with 0, 10, 20 and 30% RSW proportions at mesophilic temperature of 32ºC. Co-digestion of WH with 30% RSW proportion improved biogas yield by 113% from 19.15 to 40.85 CH4 ml/(gVS) at 50 days of co-digestion. It also exhibited the most stable daily biogas production and the largest biogas yield. The biomethanation data were fitted with the first order kinetics, modiﬁed Gompertz and the Logistic models. Biogas production for co-digestion of WH with 30% RSW proportion was best described by the modified Gompertz model with a biogas yield potential, Mo, of 43.2 ml (gVS)-1d-1; maximum biogas production rate, Rm, of 1.50 ml (gVS)-1d-1; and duration of lag, λ, of 3.89 d.